Asymmetric fault voltage support scheme for soft open points based on improved negative sequence voltage outer loop - Xuze WANG; Wu CHEN; Haixi ZHAO; Shi CHEN (电力工程技术, 2025)
Flexible interconnection and dynamic power flow regulation in distribution networks are achieved by soft open point (SOP), optimizing the configuration and scheduling of distribution resources. To improve the load voltage during asymmetric ground faults, it is proposed that positive and negative sequence currents are output by the converter during faults. This provides voltage support and enhances fault ride-through capability. However, actual operating conditions make open-loop optimization schemes susceptible. Poor performance is shown by traditional negative sequence voltage-based closed-loop support. In this paper, the conventional negative sequence voltage outer loop is improved by controlling the amplitude of negative sequence current to suppress the negative sequence voltage. The phase of the negative sequence current is adjusted to optimize the suppression effect. To enhance the inverter's capacity utilization and limit active power fluctuations, a comprehensive scheme is proposed for limiting the positive and negative sequence current amplitudes. A short-circuit fault simulation is constructed using PSCAD simulation software, based on the actual parameters of the distribution network. The simulation results show that the proposed control strategy significantly enhances voltage performance during fault conditions, improving the low-voltage ride-through capability.